TINDAK TUTUR ILOKUSI DALAM FILM KELUARGA CEMARA 2 KARYA ISMAIL BASBETH - Iin Kartini; Isnaini Leo Shanty; Legi Elfitra (Universitas Batanghari, 2024)
This research discusses the use of illocutionary speech acts in the film Family Cirrus 2 by Muhammad Irfan Ramli. The aim of this research is to describe illocutionary speech acts in the film Fir Family 2. The method used in this research is descriptive qualitative. The data in this research are in the form of words or sentences contained in illocutionary speech acts in the film Fir Family 2. The data collection techniques used to obtain data are documentation techniques and note-taking techniques. The validity of the data used to test the data obtained is observer diligence and source triagulasion. The data analysis technique used is content analysis technique by reading, analyzing, describing and concluding the content of the film Keluarga Cemara 2. The results of this research are that there are illocutionary speech acts in the form of 1) Assertive Speech Acts, 2) Directive Speech Acts, 3) Commissive Speech Acts, 4) Expressive Speech Acts, 5) Declarative Speech Acts